Rate of convergence for Szász-Bézier operators - Gupta Vijay (Український математичний журнал, 2005)
We estimate the rate of convergence for functions of bounded variation for the Bezier variant of the Szasz operators Sₙ,ₐ(f,x). We study the rate of convergence of Sₙ,ₐ(f,x) for the case 0 < α < 1.